EVALUASI IMPLEMENTASI KEBIJAKAN PROGRAM DESA TANGGUH BENCANA DALAM PERSPEKTIF HEXAHELIX ASSESSMENT DI DESA KEPUHKIRIMAN KECAMATAN WARU KABUPATEN SIDOARJO - Naufalariiq Vadio Samsuddin; Sri Roekminiati; Ika Devy Pramudiana; Sapto Pramono; Aris Sunarya (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
The Disaster Resilient Village (destana) program policy is one of the programs initiated by BNPB to increase community capacity in disaster management. The purpose of this research is to describe and analyze the data: 1) To present a description and analysis of how the implementation of Destana in Kepuhkiriman Village, Krian Subdistrict, Sidoarjo Regency in the perspective of Hexahelix Assessments 2) To present a description and analysis of the factors that contribute to the success and/or failure of the Destana policy. 3) To present a description and analysis of how Destana implementation is evaluated. This research uses implementation indicators from Edward III, in the perspective of Hexahelix Assessments, which then the results of the implementation will be evaluated using indicators from Willim N. Dunn. This research uses the analysis method according to Miles & Huberman. This research uses a qualitative approach, data collection techniques based on interviews, documentation and observation. The results showed that the implementation of the Disaster Resilient Village program in Kepuhkiriman village was still not going well enough because Destana's communication with hexahelix elements was only limited to formality, in resources it was sufficient because it had 40 volunteers, in disposition it was good enough, it was just that it had never had activities, and the bureaucratic structure had the right people. In terms of effectiveness, Destana as a form of building the resilience of rural communities is very effective. For the efficiency of Destana formation, it is the responsibility of the government to make policies that can be felt and carried out by the community. In terms of adequacy, it is still considered insufficient in the aspect of facilities and infrastructure, in the aspect of equity with the recruitment of volunteer members who are divided based on RW representatives, it is quite even. Then in the aspect of community responsiveness in realizing the potential for disasters in the village which then formed Destana was good enough.